1999
DOI: 10.1017/s0021932099000292
|View full text |Cite
|
Sign up to set email alerts
|

Nature, Nurture and First Sexual Intercourse in the Usa: Fitting Behavioural Genetic Models to Nlsy Kinship Data

Abstract: Fisher (1930) presented both theoretical and empirical results concerning genetic influences on fertility. Since then, only sparse research has been done on the genetics of fertility, although more sophisticated methodogy and data now exist than were available to Fisher. This paper presents a behavioural genetic analysis of age at first intercourse, accounting for genetic, shared environmental, and selected non-shared environmental influences. The data came from the nationally representative National Longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 0 publications
7
58
1
1
Order By: Relevance
“…The simple fact that we (as well as Neiss et al [2002]) found relatively small heritability in AFB is one example of this. Recent studies have documented important and systematic genetic variance underlying many other fertility variables, including age at first attempt to get pregnant (Rodgers, Kohler, et al 2001), ever having a child (Kohler et al 1999), fertility motivation (Rodgers and Doughty 2000), age at first intercourse (Miller et al 1999;Rodgers, Rowe, and Buster 1999), and marriage (Trumbetta and Gottesman 2000), and there have been a number of studies of direct fertility variables such as completed family size (Kohler et al 1999;Rodgers, Kohler, et al 2001;Christensen et al 2003;Rodgers, Bard, and Miller 2007;see Rodgers, Kohler, et al 2001 andKohler et al 2006 for summaries). One partial explanation for this lower heritability is that AFB may have substantially more random variation contained in its measure than other fertility variables.…”
Section: Discussion Substantive Findings and Interpretationsmentioning
confidence: 99%
“…The simple fact that we (as well as Neiss et al [2002]) found relatively small heritability in AFB is one example of this. Recent studies have documented important and systematic genetic variance underlying many other fertility variables, including age at first attempt to get pregnant (Rodgers, Kohler, et al 2001), ever having a child (Kohler et al 1999), fertility motivation (Rodgers and Doughty 2000), age at first intercourse (Miller et al 1999;Rodgers, Rowe, and Buster 1999), and marriage (Trumbetta and Gottesman 2000), and there have been a number of studies of direct fertility variables such as completed family size (Kohler et al 1999;Rodgers, Kohler, et al 2001;Christensen et al 2003;Rodgers, Bard, and Miller 2007;see Rodgers, Kohler, et al 2001 andKohler et al 2006 for summaries). One partial explanation for this lower heritability is that AFB may have substantially more random variation contained in its measure than other fertility variables.…”
Section: Discussion Substantive Findings and Interpretationsmentioning
confidence: 99%
“…Third, we have evidence of concurrent validity by using findings based on these kinship links and comparing them to those from other studies. For example, compare results on age-at-first-intercourse from Rodgers, Rowe, and Buster, (1999) Offspring Generation Sample-Bi-annual assessments of the children of women in the NLSY79 began in 1986, with an initial response rate of 95% and subsequent average response rate of 90% (Chase-Lansdale, Mott, Brooks-Gunn, & Phillips, 1991). In 1986, 95% of the biological offspring of NLSY79 mothers were assessed.…”
Section: Methods Samplementioning
confidence: 99%
“…Third, we have evidence of concurrent validity by using findings based on these kinship links and comparing them to those from other studies. For example, compare results on age-at-first-intercourse from Rodgers, Rowe, and Buster, (1999), to the molecular genetic results from Miller et al, (1999); compare Rodgers, Buster, & Rowe's (2001) delinquency patterns to those in Miles and Carey (1997); or compare the multivariate patterns across education and IQ in Neiss, Rowe, and Rodgers (2002) to those from Tambs et al, (1989).…”
Section: Methods Samplementioning
confidence: 99%
“…In male twins older than 40, genetic influences accounted for very little variation in age at first sexual intercourse variance and shared environment explained over 40%. Rodgers et al (1999) examined genetic influences on age at first sexual intercourse in a sample of 3400 twin, full-and half-sibling, and cousin pairs drawn from the National Longitudinal Survey of Youth (NLSY), which began in 1979 when respondents were 14 to 21 years of age. Collapsing across race, genetic influences explained between 10% and 20% of variation in at age at first intercourse in female pairs, with shared environment accounting for nearly 30%.…”
Section: Twin Research and Human Genetics June 2007mentioning
confidence: 99%